Financial Performance Evaluation Using Factor Analysis: A Case of J University - Hou, Yuyan; Abdul Halim, Hazianti; Basri, Mohd Faizal (International Business Education Journal, 2022)
The main purpose of this paper is to build financial performance indicators and financial performance evaluation methods suitable for local universities, and to conduct an empirical analysis of local university's financial performance evaluation. With that objective, this paper reviews the literature on indicators and evaluation methods of financial performance in universities, constructs financial performance indicators of the university using factor analysis, and evaluates local university's financial performance based on J University's data. The research shows that: Firstly, the core factors that affect the financial performance of universities are teaching factors and scientific research factors. Secondly, the financial performance indicators mainly include the per funds for staff, the proportion of full-time teachers and staff, the input of funds per student, scientific research income per full-time teacher, proportion of scientific research income to total income, the employment rate of graduates, the number of graduates, number of Humanities and social sciences, number of natural science projects, the annual growth rate of teaching activities income. Thirdly, the financial performance indicators and evaluation model constructed by factor analysis can evaluate J University's financial performance.